Peran Ibu Pada Pengasuhan dengan Pertumbuhan Balita Usia 2-3 Tahun - Nurhakim Yudhi Wibowo; Susi Muryani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
AbstractIntroduction: the toddler period has a strong foundation of gross motor skills, fine thinking, thinking, speaking and mental growth that is ready to be built.Objective: analisys purpose the relationship between motherhood and parenting growth of toddlers aged 2-3 years in slarang lor village.Method: this study used a type of quantitative research. The sample of this study was 46 respondents with total sampling. The research tool used questionnaires and observation sheets.Results: the results of the study with kendall tau showed that the role of mothers was good as much as 30 (65.2%) and normal toddler growth as muchas 36 (78.3%). It was obtained that p value = 0.954 which means p > 0.05 showed that there was no relationship.Conclusion: the conclusion from this study is that normal toddler growth can be influenced by the mother’s role, especially in parenting.